Odnosi študentov in študentk z njihovimi starši, prijatelji in romantičnimi partnerji - Cugmas, Zlatka (Psihološka obzorja (Ljubljana), 2011)
The purpose of the study, which included 180 college students from the first three years of study on different faculties, was to investigate the correlations between their relationships (trust, open communication and alienation) with their mothers, fathers, friends and romantic partners; correlations between these relationships, attachment style on romantic partners, characteristics of past romantic relationships and openness towards parents and romantic partners. For the purpose of study the relationships with parents, friends and romantic partners we translated and adapted Inventory of parent and peer attachment IPPA (Armsden & Greenberg, 1987). Attachment styles were measured using their descriptions. We developed the scales of characteristics of the subjects' romantic relationships and openness towards their parents and partners. The results showed significant positive relations between subject's quality relationships with his/her partner, secure attachment style, and quality relationships with friends and parent. Subjects with different attachment styles significantly differed in the characteristics of their romantic relationships. The results showed some significant gender differences. Female subjects had more quality relationships with their mothers, friends and partners than male subjects.
Keywords: student; students; študenti; attachment behavior; attachment theory; navezanost; marital relations; partnerski odnosi; starši; parents; friends; prijatelji; Vprašalnik navezanosti na starše in vrstnike (IPPA); Inventory of parent and peer attachment (IPPA); Ocenjevalna lestvica o značilnostih preteklih romantičnih zvez; Ocenjevalni lestvici odkritosti do staršev in do partnerja; Stili navezanosti na partnerja